Makna Gramatikal Pada Novel Cinta Dua Kodi Karya Asma Nadia - Indana Zulfa Rommadonia (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The word semantics or in English semantic etymologically comes from the Greek sema in its nominative form which means 'sign' or in its verb form samaino which means 'mark' or 'mean' or 'symbolise'. Indonesian must be used properly in accordance with the Indonesian language order that has been regulated and systemised. According to Chaer 2012: 266 that a complete sentence is formed from language units that have the highest position is discourse. Grammatical meaning is the meaning that is present as a result of grammatical processes such as affixation processes, reduplication processes, and composition processes." The purpose of this research is to know and understand what is meant by grammatical meaning, novels, and understand the analysis of grammatical meaning in the novel entitled Cinta Dua Kodi Karya Asma Nadia. In other words, from this research we can find out how many compound words in the novel Cinta Dua Kodi Karya Asma Nadia on pages 1 to 95. In addition, this research is descriptive qualitative, descriptive qualitative method is used to examine every word, sentence, and paragraph that is used as a quotation technique to be analysed. Based on the results of the research, it can be concluded that in the novel entitled Cinta Dua Kodi Karya Asma Nadia on pages 1 to 95 there are 10 compound words.